Pengaruh Government Effectiveness Index dan Foreign Direct Investment terhadap GDP di Negara Asia Selatan - Rahmadiani, Austine; Nairobi, Nairobi; Darmawan, Arif (Universitas Pasundan, 2023)
Analyzing the effect of Government Effectiveness Index and Foreign Direct Investment for GDP in South Asian countries is the objective of this study. The analytical methodology employed during this work is panel data regression. GDP is a dependent variable, whereas the Government Effectiveness Index and Foreign Direct Investment are independent variables. In this study, the Fixed Effect Model proves to be the most practical model. Its results indicate that South Asia's GDP is marginally and insignificant positively impacted by the Government Effectiveness Index. Then, foreign direct investment has a negligible and has a insignificant positive impact on the GDP of South Asia. Likewise, result of model indicates that the combination of the Foreign Direct Investment and Government Effectiveness Index variables affects the GDP of South Asia.